FAKTOR PENYEBAB RADIKALISME DI INDONESIA - Abdul Munjid, Mohammad; Baedhowi, Baedhowi; Khoirina, Rusyda (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2022)
This study analyzes what drives Radicalism in Indonesia. Many argue between groups about their respective understandings, even though they are of the same religion. In today's era, this is good news for us, because knowledge in the fields of technology, science, medicine, progress very rapidly for Muslims, but in the field of morals, morals, social and even economics in Islam, it has a negative impact on radicals. This is because the group monitors their religious texts or texts based on their ratios or lusts without wanting to look at the arguments of naqli or aqli, so that in appreciating the ratio they often go too far. Keywords: Causing Factors, Radicalism